Ormocer: An aesthetic direct restorative material; An in vitro study comparing the marginal sealing ability of organically modified ceramics and a hybrid composite using an ormocer-based bonding agent and a conventional fifth-generation bonding agent - Sarika Kalra; Arundeep Singh; Manish Gupta; Vandana Chadha (Wolters Kluwer Medknow Publications, 2012)
Aims and Objectives : To compare the marginal sealing ability of ormocer with a hybrid composite using an ormocer based bonding agent and a conventional fifth generation bonding agent. Materials and Methods : Fifty four human premolars were randomly distributed into four test groups of 12 teeth each and two control groups of 3 teeth each. Class I occlusal preparation of 1.5 mm depth were made in each tooth. These were restored using the adhesive and restorative material according to the group. The restorations were finished using a standard composite finishing and polishing kit. Thermocycling between 5 o C and 55 o C was carried out. Having blocked the root apex and the entire tooth surface except 1 mm around the restoration margin, the teeth were immersed in 2% methylene blue for 48 hours, after which the dye penetration through the margins of each sample was studied under a stereomicroscope. Results and Discussion : Group IV (Admira with Admira Bond) showed the minimum marginal leakage with a mean of 0.200 mm. Four samples in this group showed no microleakage at all and a maximum of 0.400 mm was seen in one sample. Group II (Spectrum TPH with Admira Bond) showed the maximum leakage with a mean of 0.433 mm. One sample showed as much as 1.00 mm of microleakage. Admira when used with Admira Bond showed lesser microleakage than Spectrum TPH used with Prime & Bond NT, the difference being statistically insignificant.